THE DEVELOPMENT AND VALIDATION OF CRITICAL AND CREATIVE THINKING SKILLS TEST IN ENZYME FOR UNDERGRADUATE CHEMISTRY STUDENTS - Wahyudi, Andi; Liliasari, S; Supriyanti, FMT; Nahadi, Nahadi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The aim of this study was to develop and validate a test of students’ critical and creative thinking skills on enzyme. This study was conducted using development and validation methods through six steps, i.e. (1) defining the construct and formulating objectives, (2) formatting items, (3) constructing items, (4) creating a scoring guide, (5) Judging items by experts, and (6) calculating validity, reliability, level of difficulty and discrimination by empirical study. This test was constructed two-tier test, which consists of the first tier as a multiple choice and the second tier as the reason from the first tier option. The participants were 61 undergraduate chemistry students who studied enzyme in a chemistry department. The results showed that item CVI value was 0.86 and item Cronbachs’ Alpha value was 0.843 (very high category). Item difficulty index (P) was 0.501, and Item discrimination index (D) was 0.328 which showed that the level of difficulty item in the medium category and level of discrimination in the good category. Out of initial 14 items, 3 items were excluded after the analysis of CVI, item difficulty index and item discrimination index. The revised 11-item test was found to have sufficient validity, reliability, item difficulty index and item discrimination index to measurement of enzyme concept mastery, critical thinking skills, and creative thinking skills.